Mini Review: The Competencies of Christian Religious Teacher - Yudha Nata Saputra (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
The purpose of this study was to obtain information about the competence of Christian religious education teachers and factors related to the competence of PAK teachers by using the systematic literature review method. The results of the study found that the competence of PAK teachers was above the average but their professional competence was still below the average. There are a number of factors related to the competence of PAK teachers, namely Student Learning Behavior with Problems, Self-Identity as a servant of God, Student Learning Motivation, Student Creativity, Student Learning Achievement, and Commitment. When viewed from the magnitude of the correlation coefficient with the PAK Teacher Competency Variable, sequentially, the Student Learning Achievement Variable has a correlation coefficient of 0.794, the Self Identity Variable as a Servant of God is 0.715, the Student Motivation Variable is 0.611, and the Commitment Variable is 0.259. Then when viewed from the magnitude of the influence given, the competence of the PAK teacher has an influence in overcoming problematic student learning behavior by 64.9%, on student learning motivation by 37.3% and on student learning creativity by 20.01%.